Experimental study of internal solitary wave evolution beneath an ice keel model - Wang, Guanjing; Du, Hui; Fei, Jianfang; Wang, Shaodong; Xuan, Pu; Guo, Hailong; Xu, Junnan; Gu, Zhiyuan (Frontiers in Marine Science, 2024)
Internal solitary waves (ISWs) propagating in polar seas are affected by the sea ice at upper boundary of seas and thus exhibit complex evolution characteristics. Herein, spatiotemporal changes in the wave element, flow field, and energy of ISWs beneath an ice keel model were investigated to examine the evolution of ISWs. For this purpose, laboratory experiments were conducted using dye-tracing labeling, conductivity probes, Schlieren technology, and particle image velocimetry. The results show that ice keel causes an increase in the thickness of the pycnocline and even the occurrence of breaking and internal surging of ISW. Additionally, the waveform becomes narrower or wider at different positions, and wave amplitude and speed decrease, with a maximum reduction 30%–40%. Furthermore, the ice keel strengthens the shear of the ISW-induced flow field, generating vortices and mixing. The energy of ISWs undergoes internal conversion majorly at the front slope of the ice keel, while energy dissipation occurs largely at the back slope, with dissipation rates as high as 60%.